„The Life of Matvei Kozhemyakin” by Maxim Gorky: Reflecting on the Genre - Szymonik, Danuta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The paper takes up the problem of the genre of Maxim Gorky’s novel/novella The Life of Matvei Kozhemyakin (1911). The author of the article finds the discussed work synthetic in terms of genre, indicating features of various genres (annals, saga, autobiography, several varieties of the novel, including historical, social, and family novel) which form in it a harmonious artistic whole. Following the interpretations of Jerzy Lenarczyk, Ivo Pospíšil and other scholars, the author of the article puts forward the family saga as the predominating generic component and emphasizes that “the family idea” (mysl semeinaia) influenced many of Gorky’s works and shaped their generic structure.